Convergences and divergences between scientific and Indigenous and Local Knowledge contribute to inform carnivore conservation - Torrents-Ticó, Miquel (Ambio, 2021)
There is increasing recognition that diverse knowledge systems can work in mutually enriching ways and that Indigenous and Local Knowledge (ILK) can enhance biodiversity conservation. However, studies using scientific knowledge and ILK in a complementary manner, and acknowledging convergent and especially divergent insights have remained limited. In this study, we contrasted proxies of abundances and trends of threatened and conflict-prone carnivores (caracal, cheetah, jackal, lion, leopard, spotted hyaena, striped hyaena) derived separately from scientific knowledge and ILK. We conducted camera trapping, track surveys and semi-structured interviews with local pastoralists from northern Kenya. We found convergences highlighting the need for conservation action and divergences suggesting scientific ecological sampling limitations or underlying socio-psychological phenomena. Overall, our study shows that complementing scientific knowledge and ILK as separate sources of information and opening up space for discrepancies can enrich our understanding of the status and trends of carnivores, as well as recognizing human-carnivore relationships. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s13280-020-01443-4) contains supplementary material, which is available to authorized users.